HSCT FOR CHRONIC MYELOPROLIFERATIVE DISEASES: Primary myelofibrosis, polycythemia vera, essential thrombocythemia - Funke, Vaneuza Araújo Moreira; Colella, Marcos Paulo; Macedo, Antonio Vaz de; Teixeira, Gustavo Machado; Ribeiro, Andreza Alice Feitosa; Vigorito, Afonso Celso (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2021)
THE BRAZILIAN SOCIETY FOR BLOOD AND MARROW TRANSPLANTATION (SBTMO) PRESENTS THE BRAZILIAN GUIDELINES ON HEMATOPOIETIC STEM CELL TRANSPLANTATION